2005
DOI: 10.1097/01.ju.0000147747.89028.64
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Vesicoureteral Reflux in Patients With Self-Retaining Ureteral Stents: Implications for Upper Urinary Tract Instillation

Abstract: VUR is not a guaranteed consequence of Double-J stent placement. Therefore, when upper urinary tract instillation with the Double-J technique is considered, a cystogram should be performed first to confirm the occurrence of reflux, determine the intravesical volume required to induce reflux and ascertain that the pertinent section of the ureter or pelvicaliceal system from which the tumor was initially removed is opacified during study. An interval that remains to be defined should be allowed between stent ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Yossepowitch et al used performed cystograms with an indwelling stent in place and reported that retrograde flow occurred in only 56% of patients. Additionally, the mean minimal intravesical volume to obtain reflux was 170 mL, which is higher than the typically instilled treatment volume [10]. …”
Section: Bcgmentioning
confidence: 99%
“…Yossepowitch et al used performed cystograms with an indwelling stent in place and reported that retrograde flow occurred in only 56% of patients. Additionally, the mean minimal intravesical volume to obtain reflux was 170 mL, which is higher than the typically instilled treatment volume [10]. …”
Section: Bcgmentioning
confidence: 99%
“…On the other hand, depending solely on passive retrograde flow through an indwelling stent might not be beneficial. Yossepowitch et al reported that only 56% of patients with an indwelling stent demonstrated passive reflux after intravesical instillation, at volumes almost fourtimes the normal treatment volumes used for intravesical therapy (mean: 170 ml) [24]. Thus, it is prudent not only to confirm reflux using contrast material, prior to initiation of therapy, but also to establish the volume needed by which reflux all the way up to the renal pelvis is noted.…”
Section: Diagnosis Treatment and Follow-upmentioning
confidence: 96%
“…13 Furthermore, immediate measurements of the minimal required volume were significantly higher than late measurements (255 mL and 146 mL respectively, P <.001). 27 Thus, patients who receive maintenance topical therapy might require confirmation of minimal volume for VUR with each instillation, making this approach a potentially unreliable method of upper tract delivery.…”
Section: Commentmentioning
confidence: 99%